Demographic Determinants of Patient Satisfaction: A Study on Age, Gender, Marital Status, Education, and Profession in Hospital Management - Khatri, Rasu; Bista, Dr. Sita; Poudel, Iru (International Journal of Atharva, 2024)
This study explores the relationship between demographic variables and patient satisfaction with hospital management in Kathmandu. Utilizing a descriptive and correlational research design, data were collected from a sample of 72 patients aged 15-45 through a structured questionnaire comprising 27 questions. The demographic variables analyzed include age, gender, marital status, education level, and profession. Results revealed weak and statistically insignificant correlations between these demographic factors and patient satisfaction, suggesting that other elements may influence patient experiences more significantly. The study underscores the need for hospital management to consider various factors to enhance patient satisfaction.